Evaluating the Impact of Social Networks on Human Communication in the Digital Era - Barge Gul Khalili; Tamanna Quraishi; Fatana Dayan (Tinta Emas Institute, 2024)
The widespread adoption of social networks has significantly transformed human communication and interaction patterns in contemporary society. The purpose of the study is to examine how individuals perceive and experience social network usage, aiming to shed light on its implications for interaction frequency, communication styles, social unity, collective action participation, and overall well-being. Employing an observational and descriptive research design, data was collected from a diverse sample of 120 participants using surveys administered online or in-person. Convenience sampling techniques ensured a balanced representation across age groups, genders, occupations, and geographical locations. Data analysis involved a combination of quantitative and qualitative approaches, with descriptive statistics summarizing demographic characteristics and survey responses. Thematic analysis was employed to identify recurring themes and patterns in qualitative data. Results reveal diverse perceptions regarding social network impact, with Facebook emerging as the most preferred platform for human communication. Participants reported varying levels of interaction frequency, communication styles, and concerns about negative effects on mental health. In conclusion, the study underscores the nuanced nature of social network dynamics and their implications for human communication and well-being. Recommendations include promoting digital literacy and mindfulness to mitigate potential negative impacts while harnessing the positive aspects of social network usage for enhancing social connections and community engagement.